Thenar Atrophy and Syncope as Signs of Thoracic Outlet Syndrome (TOS): A Clinical Electrophysiological Exploration of Three Cases - Musa, Juna; Compres, Luis; Valdez, Adriano; Puello, Adrian; Rakovica, Loran; Guy, Ali; Rahman, Masum; Martinez, Barbara; Kola, Ina; Blanco, Ruben (Archives of Clinical and Medical Case Reports, 2020)
Thoracic outlet syndrome (TOS) is a rare disease that presents with neurogenic and vascular symptoms and is caused by compression of the brachial plexus and/or subclavian vessels as they pass through the cervico thoraco brachial region. However, making the diagnosis of TOS can be challenging due to a lack of standardized objective confirmatory tests. We present three cases of neurovascular TOS where electrophysiological exploration was conducted to develop the diagnose. <gdiv></gdiv>